The relationship between work life balance and quality of life at Pejabat Tanah dan Jajahan Tanah Merah, Kelantan / Norizan Mohamad@Alias - Mohamad@Alias, Norizan (2016)
The purpose of this research is to identify the relationship between work life balance and quality of life. This study has three objectives include flexibility working hours, child care support and telecommuting is perceived to be the most significant relationship in determining quality of life. The sample size use for this study is 40 and from 100 of populations, only 40 sample size used for the actual survey based on Krejcie & Morgan table for determining sample size from a given population. The questionnaire has been distributed to all supports employees in Pejabat Tanah dan Jajahan Tanah Merah, Kelantan and about 40 respondents have answered the questionnaires distributed. Social Science Software (SPSS) version 22 is used to analyze the results collected. Based on the finding of this research there is a significant relationship between work life balance and quality of life at Pejabat Tanah dan Jajahan Tanah Merah, Kelantan (PTJTM). In order to make some improvement to the employees in PJTJM., some recommendation and recommendation for the future research was stated.